The Role Of Digital Health Technology In Enhancing Health Promotion Campaigns : A Case Study From A Resource Imites Region - Rita Rena Pudyastuti; Johanna Tomasoa; Andrias Horhoruw; Marta Atik Martsiningsih (PT. Anagata Sembagi Education, 2024)
Study This evaluate role technology digital health in increase effectiveness campaign promotion health in the region with source Power limited use method studies literature . Focus main is understand contribution application health , social media platforms , and services message short (SMS) in expand reach and impact information health , as well as identify challenges and solutions related its application . This method involving review systematic to relevant literature , including​ article journal , report research , and publication about technology digital health . Analysis aiming collect data about effectiveness technology , challenges faced, and strategies implemented . Findings show that technology digital health has the potential big in repair access information health , improve awareness society , and encourage behavior healthy. Limitations internet access and low digital literacy can hinder utilization technology. The proposed solution covering investment in infrastructure technology information , improvement digital literacy through training , and work The same between government , sector private sector , and non- governmental organizations . Technology digital health can become tool effective in reach objective health a more society good and even , especially in areas with source Power limited , with support and planned strategies. Research This give outlook about optimization technology digital health based proof studies literature For results better health​ Good .